Evaluasi Efektivitas Pengendalian Risiko Atas Penjualan Property Di PT X - Putri, Aulia Yunianti; Kurniawan, Aceng (Jurnal Online Manajemen ELPEI, 2024)
The progress and development of the business environment today have evolved rapidly and precisely. The increasingly competitive industrial development over time necessitates every company to be ready to face intensifying competition. Essentially, risks are inherent in all aspects of human life and activities, from personal matters to corporate affairs, from lifestyle issues to disease patterns, from waking up to sleeping at night, and much more. Risk management experts, both domestically and internationally, have various definitions of what risk and risk management entail. However, generally, risk can be defined in various ways, such as an adverse event or a deviation of outcomes from expectations. This research employs a descriptive qualitative approach to evaluate the effectiveness of risk control in sales at PT "X" Property Company. The findings indicate that the process of property sales begins with negotiations between the property owner and prospective buyer regarding price and payment terms, followed by the buyer transferring earnest money to demonstrate transaction seriousness and drafting a purchase agreement. Subsequently, involving a notary for the transfer of property title with agreed-upon costs, and after completing all administrative tasks and payments, the transaction is deemed valid. On the other hand, PT. X has successfully implemented risk control in property sales, albeit with some shortcomings that need to be addressed, particularly concerning secret selling practices that undermine business integrity. Proactive measures, such as implementing secure reporting mechanisms for employees, aid in preventing such practices, while direct monitoring by the owner enables quick detection and handling of unethical behavior.